KEJADIAN TB PARU DI KOTA DEPOK - Rosyanti, Intan; Kusumaningtiar, Devi Angeliana (Health Publica, 2020)
Tuberculosis (TB) is an infectious disease caused by infection with the bacterium Mycobacterium Tuberculosis. The number of cases of pulmonary TB that occurred at Cipayung Depok Health Center increased by 6.89% from 2016 to 2017. The type of research used was quantitative with a case control design. The study sample used a ratio of 1: 2, with a sample of 41 people and a control sample of 82 people. Data collection using a questionnaire. Statistical test used Chi-Square test. Based on the Chi-Square test results showed that age (p = 0.154) and BCG immunization (p = 0.437) have no association with the occurrence of pulmonary TB disease. Sex (0.004), economic status (p = 0.018), contact history (p = 0.001), and smoking behavior (p = 0.001) have association with the occurrence of pulmonary TB disease. It is suggested that the Puskesmas should consider creating an anti-TB male community, adding free milk to TB patients with low economic status if they are still malnourished, making a special day for free mask distribution, establishing a smoking clinic, and for TB patients to always wear masks especially when interacting with other people, closing your mouth when coughing and not throwing phlegm carelessly.Keywords : pulmonary TB, age, sex, BCG immunization, economic status, contact history, smoking